FEATURES OF THE STRUCTURE OF THE FACIAL SKULL IN PATIENTS WITH AGENESIS OF THE UPPER LATERAL INCISORS IN CASE OF MESIAL OCCLUSION WITH NORMAL MANDIBLE POSITION - Skrypnyk, І.L.; Shnaider, S.A.; Gorokhivskiy, V.N.; Suslova, O.V.; Dienga, A.E.; Kordonets, O.L.; Rachynskyi, S.V. (World of Medicine and Biology, 2024)
The research is devoted to the study of the characteristics of the correspondence of the size of the teeth and dentition of the upper and lower jaw and the structure of the facial skull in patients with agenesis of the upper lateral incisors in the mesial bite. The study involved 55 patients who applied to the Department of Orthodontics of the Bogomolets National Medical University aged 9 to 23 years with agenesis of both lateral incisors of the upper jaw, the absence of transverse anomalies and mesial occlusion (class III according to Engle) with normal mandibular position. In patients with upper lateral incisor agenesis and mesial occlusion, significant narrowing and shortening of the maxillary dentition, especially in the area of premolars and molars, as well as narrowing of the apical base of the maxilla were observed. The average values of the ANB angle and the WITS index indicate the presence of a skeletal mesial occlusion accompanied by occlusion disorders and malposition of the central incisors, which requires an individual approach to diagnosis and treatment planning.
Keywords: mesial bite; teeth; orthodontics; lower jaw; skull